PENGETAHUAN PERSONAL HYGIENE DENGAN PERILAKU PENCEGAHAN KEJADIAN LEPTOSPIROSIS DI KOTA BIMA NTB - Yulian Endarto (Jurnal Delima Harapan, 2020)
ABSTRACT Background: Leptospirosis is an infectious disease caused by leptospirapatogen bacteria. The highest leptospirosis disease in the African region (85.5 per 100,000 population) was followed by the Western Pacific (66.4), America (12.5), Southeast Asia (4.8) and Europe (0.5). Most of the reported cases have severe manifestations, whose mortality rate is greater than 10%. Objective: This study aimed the relationship of knowledge and attitude of PHBS with behavior prevention of Leptospirosis event on kota Bima Nusa Tenggara Barat. Method: The methods of this research used quantitative descriptive with cross sectional design consisting of 71 samples were obtained. Statistical analysis using t test. Result: There is a significant correlation coefficient of t test of 0.37 and the Sig value of 0.000 where the resulting significance value is less than 0.05 (Sig. P 0,000 <0,05) thus there is a relationship of knowledge and attitude of PHBS with the prevention behavior incidence of leptospirosis on Kota Bima Nusa Tenggara Barat. Conclusion: There is a significant relationship of knowledge and attitude of PHBS with behavior prevention of leptospirosis incidence in Kota Bima Nusa Tenggara Barat. Keywords : Knowledge, Attitude, PHBS, Behavior, Leptospirosis